Myocarditis as the first manifestation of eosinophilic granulomatosis with polyangiitis - Đorđević-Radojković Danijela; Apostolović Svetlana; Damjanović Miodrag; Kostić Tomislav; Fejsa-Levakov Aleksandra; Dimitrijević Marko; Janković-Tomašević Ružica; Dakić Sonja; Božinović Nenad; Pavićević Milena (Vojnosanitetski Pregled)
Introduction. Myocarditis is not a rare diagnosis, but its etiology often remains unknown as it requires extensive diagnostic work. Eosinophilic granulomatosis with polyangiitis (EGPA) or Churg-Strauss syndrome is a very rare systemic disease that is not easy to diagnose. Myocarditis in EGPA is uncommon and usually occurs in the late stages of the disease. Case report. A 22-year-old man was admitted with acute coronary syndrome. Using coronary angiography, the presence of stenoses on the epicardial coronary arteries was ruled out, and a working diagnosis of myocardial infarction with non-obstructive coronary arteries (MINOCA) was established. Then, we found inflammatory syndrome, eosinophilia, and a lot of systemic symptoms and signs. The diagnostic work included extensive laboratory tests, which ruled out infectious agents. Then, immunological tests, a computed tomography scan of the chest, cardiac magnetic reso-nance imaging (MRI) and a biopsy of the bone marrow, nasal mucosa, and skin were performed. We managed to establish the diagnosis of myopericarditis by cardiac MRI. The cause of myocarditis – EGPA, was found only after the histopathological finding of the skin biopsy, which enabled ad-equate immunosuppressive therapy. Conclusion. The accurate diagnosis was crucial for the correct, causal treatment of the patient, especially because he needed life-long immunosuppressive therapy. In order for such complex patients to receive adequate treatment, a multidisciplinary approach and perseverance in the diagnostic evaluation of the etiology of myocarditis are necessary.